THE HONEY CONSUMPTION TO HAEMOGLOBIN CONTESTS WHEN MENSTRUAL AT TEENAGE OF PRINCIPLES - Catur Prasastia lukita Dewi; Husnul Hatimah (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2018)
Menstruation is one factor that can reduce hemoglobin levels in young women. Hemoglobin is a protein in the form of an iron-rich oxygen-carrying pigment. Pharmacological therapy that can increase hemoglobin levels include the consumption of honey. This study aims to determine the effect of honey consumption on changes in hemoglobin levels during menstruation in adolescent girls at Ma'had Aly Pondok Boarding School Salafiyah Syafi'iyah Sukorejo Situbondo Year 2017 This research design using pre-experiment design. A sample of 15 respondents who confirm the inclusion criteria. Sampling technique is by proportional stratified random sampling . From the 15 respondents , all of them in the given consumption of honey . The data obtained were processed with SPSS 16 software. The Analysis of the data used is the Wilcoxon signed rank test trials . The results showed that the effect of honey on changes in Haemoglobin levels during menstruation in adolescent girls, performed by statistical test using Wilcoxon test with the help of SPSS for 16.0 windows obtained result p = 0,001 <Î± = 0,05. Thus Ho is rejected and H1 accepted which means there is influence of giving honey to changes of hemoglobin level during menstruation in adolescent daughter. Honey is able to increase hemoglobin levels because the iron content contained in honey is very effective in raising the levels of hemoglobin in the blood, especially during menstruation. Therefore, it is expected that honey still needs to be continued so that the risk of anemia in adolescent menstruation can be minimized